Principals without distinction - Dyson, M (Sweet & Maxwell, 2018)
Reflects on the distinctions which the law draws between participants in a crime. Examines the justifications for distinguishing: (1) between principals and accomplices, including how an "accessory" is defined; (2) between an accomplice to one crime and to further crimes; and (3) between different fault elements, especially intention, foresight of risk and conditional intention. Discusses the advantages of maintaining clearly-drawn distinctions.